Prevalence of rheumatic heart disease in Senegalese school children: a clinical and echocardiographic screening. Issue 2 (30th November 2015) - Ngaïdé, Aliou Alassane; Mbaye, Alassane; Kane, Adama; Ndiaye, Mouhamadou Bamba; Jobe, Modou; Bodian, Malick; Dioum, Momar; Sarr, Simon Antoine; Aw, Fatou; Mbakop, Prisca Sede; Ba, Fatimata Gatta; Gaye, Ngoné Diaba; et al.
Abstract : Objective: To study the prevalence of rheumatic heart disease (RHD) in schools (locally referred to as 'daaras') located in the city of Dakar and its suburbs using both clinical examination and echocardiography. Methods: This is a cross-sectional study conducted from 9 August to 24 December 2011 involving 2019 pupils, aged between 5 and 18 years selected from the 16 'daaras' of the Academic Inspectorate ( Inspection d'Académie ) of the city of Dakar and its suburbs. Anamnestic, clinical and echocardiographic data were collected and entered into a questionnaire designed for the study. The World Heart Federation criteria for echocardiographic diagnosis were used to diagnose RHD. p<0.05 was considered statistically significant in bivariate analysis. Results: About 60.1% of the pupils were men and the mean age was 9.7±3.3 years. 10 cases of definite RHD were detected, prevalence being 4.96 per 1000 (95% CI 2.4 to 9.1). This prevalence was five times higher with echocardiographic screening compared with clinical screening. 23 cases (11.4 per 1000) of borderline forms were detected. The populations at risk of definite RHD identified in our study were children over 14 years (p<0.001), those with recurrent sore throat (p=0.003) and those residing in the suburbs of the city of Dakar (p<0.001). Conclusion: Our study shows a relatively high prevalence of RHD. Reducing its prevalence should focus on the implementation of appropriate policies, targeting at-risk populations and focusing on raising awareness and early detection.